Chelidonic Acid and its Derivates: General Spectrum of Biological Activity and Osteogenic Properties (Review) - L. A. Miroshnichenko; T. Yu. Polyakova; E. Yu. Avdeeva; S. V. Krivoshchekov; I. A. Khlusov; M. V. Belousov (Разработка и регистрация лекарственных средств, 2022)
Introduction. The development and implementation of new effective and safe drugs with osteogenic activity is an urgent problem of modern medical and pharmaceutical sciences. This is due to the wide prevalence and complexity of the treatment of diseases of the musculoskeletal system, which entails significant economic costs for the treatment and recovery of this group of patients. Recently, standard therapy regimens are increasingly being supplemented with drugs derived from medicinal plants, which is associated with their rather pronounced therapeutic effect and the absence or mild side effects compared to more expensive modern medical analogues. In this regard, the development of new directions in the strategy for the development of pharmacological agents from plant sources becomes relevant. The study of plant secondary metabolites is one such area that has already yielded good results in relation to the development of such drugs, and holds great promise. The review provides information on the biological properties of chelidonic acid and its possible derivatives in order to demonstrate the prospects for the use of these objects for the development of drugs, including those with osteogenic activity.Text. Chelidonic acid is a substance present in many medicinal plants and has a wide range of pharmacological effects – analgesic, antimicrobial, anti-inflammatory, oncostatic and sedative. At the moment, methods have been developed for obtaining chelidonic acid and its derivatives from natural sources. In addition, chelidonic acid belongs to the so-called “small” molecules with osteogenic properties, which makes it promising in the creation of drugs for the treatment of diseases of the musculoskeletal system caused by impaired formation and regeneration of bone tissue. Native chelidonic acid has a low osteogenic activity, but given its ability to form complex compounds, it can act as a delivery system for osteoprotective micro- and macroelements. So, calcium chelidonate in experiments in vitro and in vivo shows a pronounced osteogenic activity: it stimulates the viability, adhesion and osteogenic differentiation of mesenchymal stem cells, enhances the mineralization of the extracellular matrix.Conclusion. Taking into account the wide range of biological activity of chelidonic acid, its use in the complex therapy of allergies, depression, diabetes mellitus, inflammatory diseases, malignant neoplasms and other pathological conditions seems relevant. Calcium chelidonate is a promising drug candidate that can be used to accelerate regeneration processes and in bone tissue engineering.